Fiscal Positions in Latin America. - Zettelmeyer, Jeromin (IMF Working Papers., 2008)
Fiscal performance in Latin America looks much improved this decade compared to the 1980s or 1990s. Is this a ""structural"" improvement or likely to be transitory? This paper answers this question by estimating the relationship between non-commodity revenue and the economic cycle, and evaluating commodity revenues using alternative medium term commodity price projections. The main result is that structural revenues have indeed improved as a share of GDP, and structural primary balances are currently in surplus in many Latin American countries. However, the magnitude of these improvements is u.